School children's backpacks, back pain and back pathologies. Issue 8 (10th March 2012) - Rodríguez-Oviedo, Paloma; Ruano-Ravina, Alberto; Pérez-Ríos, Mónica; García, Francisco Blanco; Gómez-Fernández, Dorotea; Fernández-Alonso, Anselmo; Carreira-Núñez, Isabel; García-Pacios, Pilar; Turiso, Javier
Abstract : Objective: To investigate whether backpack weight is associated with back pain and back pathology in school children. Design: Cross-sectional study. Setting: Schools in Northern Galicia, Spain. Patients: All children aged 12–17. Interventions: Backpack weight along with body mass index, age and gender. Main outcome measures: Back pain and back pathology. Results: 1403 school children were analysed. Of these, 61.4% had backpacks exceeding 10% of their body weight. Those carrying the heaviest backpacks had a 50% higher risk of back pain (OR 1.50 CI 95% 1.06 to 2.12) and a 42% higher risk of back pathology, although this last result was not statistically significant (OR 1.42 CI 95% 0.86 to 2.32). Girls presented a higher risk of back pain compared with boys. Conclusions: Carrying backpacks increases the risk of back pain and possibly the risk of back pathology. The prevalence of school children carrying heavy backpacks is extremely high. Preventive and educational activities should be implemented in this age group.